Women's entrepreneurship in Pomerania in light of available research - Julita E. Wasilczuk (Gdańsk University of Technology, Faculty of Management and Economics, 2017)
Background. Despite the fact that research on women's entrepreneurship has been conducted for many years, still many clear answers to questions about the differences between entrepreneurs of both genders are missing. Research aim. The differences in the methods of enterprise management are one of the rarely studied areas (Jennings and Brush, 2013). This fact, combined with the small number of studies dealing with female entrepreneurs in Poland, has been the main reason for writing the present text. Methods. The article reports the state of art in the women entrepreneurship research as well as the research conducted in Pomerania province in Poland. Key findings. The results of the research revealed small differences between women and men activities in the firms. The conclusions for the research and policy makers end the paper.
Keywords: J16; L25; L26; 330; women entrepreneurship; management in small business